2012
DOI: 10.1039/c2sm06476f
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable dextran based microgels: a study on network associated water diffusion and enzymatic degradation

Abstract: Sustained drug delivery represents a major challenge in nanomedicine. Solutions to the many requirements posed by this field are not easy to address using a unique delivery vehicle. In recent years, our goal has been to implement such requirements in a single device by manipulating the structural and functional features of “soft” biocompatible drug delivery platforms. In this paper we describe a set of biocompatible drug delivery materials, with controlled structure and dimension, which are both biodegradable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…The inclusion of hyaluronic acid as a constituent of the network enhances the biocompatibility and biodegradability of the construct. We have reported that in dextran/ p (methacrylate‐co‐NiPAAm) microgels the thermoresponsivity can hinder the enzyme biodegradation process above the VPTT . Moreover, high crosslinking degree affects negatively the enzyme catalyzed degradation .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of hyaluronic acid as a constituent of the network enhances the biocompatibility and biodegradability of the construct. We have reported that in dextran/ p (methacrylate‐co‐NiPAAm) microgels the thermoresponsivity can hinder the enzyme biodegradation process above the VPTT . Moreover, high crosslinking degree affects negatively the enzyme catalyzed degradation .…”
Section: Resultsmentioning
confidence: 99%
“…We have reported that in dextran/ p(methacrylate-co-NiPAAm) microgels the thermoresponsivity can hinder the enzyme biodegradation process above the VPTT. [74] Moreover, high crosslinking degree affects negatively the enzyme catalyzed degradation. [66] Considering that HA is one of the components of the extracellular matrix, which is subject to a degradation catalyzed by metalloproteinases and hyaluronidases, the systems investigated here offer the opportunity to study, preliminarily in vitro, the degradation mechanism as a function of the temperature and of the degree of crosslinking.…”
Section: Raft Polymerization Of P(nipaam) Bearing Alkyne End Groups (mentioning
confidence: 99%
“…Frequently used biocompatible and biodegradable polymers include gelatin [22][23][24], chitosan [25,26], alginate acid [27,28], hyaluronic acid [29,30], poly(lactic acid) [31], and dextran [32]. However they do not exhibit a well-characterized thermoresponsive property in general.…”
Section: Introductionmentioning
confidence: 99%
“…Dex-MA hydrogels can be rapidly generated via photo-initiated cross-linking, and the polymer itself is well-characterized and easily accessible [27][28][29] . Importantly, Dex-MA hydrogels can also be degraded under biological conditions using dextran-specific enzyme -dextranase [30][31][32][33][34][35][36][37][38][39][40][41] . Additionally, to ensure the adhesion of fabricated hydrogels to glass surface during rinsing steps, we employed methacrylate-modified glass coverslips, thus leading to covalent bonding of hydrogel objects to the surface.…”
Section: Resultsmentioning
confidence: 99%